Microwave characteristics of a pseudomorphic high electron mobility transistor under electro-optical stimulations - Kim, DM; Song, SH; Baek, KH; Kim, DJ; Kim, HJ (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2000)
Comprehensive P-opt-, V-GS-, and V-DS-dependent variations of microwave performances (f(T) and f(max)) in a PHEMT under electro-optical stimulation are reported for the first time. Under low P-opt, microwave characteristics are observed to be predominantly modulated by the photoconductive effect through the transconductance, Under high optical power, however, they are limited by the photovoltaic effect through the gate capacitance and a parasitic MESFET activated parallel to the In0.13Ga0.87As channel PHEMT, Contrary to the dc current-voltage (I-V) characteristics, which are predominantly controlled by the photoconductive effect with a strong nonlinearity due to a parallel conduction, microwave characteristics strongly depend on the photovoltaic effect as well as the photoconductive effect under electro-optical stimulation. An extended small-signal photonic-microwave model is suggested for better description of PHEMT's under electro-optical stimulations.
Keywords: MODFETS; HEMT